Favourable long‐term outcome of granulomatous colitis involving two Escherichia coli strains with multiple antimicrobial resistances in a French bulldog in Germany. Issue 1 (29th April 2016) - Mueller, Maximilliane; Dahlem, Dorothee Petra; Henrich, Manfred; Neiger, Reto; Schmitz, Silke
Abstract : A two‐year‐old female French bulldog was presented for chronic large bowel diarrhoea. The dog had been suspected to have granulomatous colitis, but no improvement was noted with enrofloxacin treatment. Diagnosis was confirmed by histology and fluorescent in situ hybridisation. Isolated Escherichia coli strains showed multiple resistances to antimicrobials, including enrofloxacin. Treatment with potentiated amoxicillin and cefovecin resulted in complete resolution of clinical signs within two weeks and treatment was continued for a total of eight weeks. The dog had no signs of large bowel diarrhoea and gained 2 kg of bodyweight within 10 months. This is the first case report of a French bulldog with granulomatous colitis with a favourable long‐term outcome despite colonisation with multiresistant adherent‐invasive E coli . This case highlights the importance of antimicrobial sensitivity testing from colonic mucosal biopsy samples in canine granulomatous colitis. It should raise awareness of this disease in continental Europe.